Information share and its predictability in the Indian stock market. Issue 10 (15th July 2019) - Karmakar, Madhusudan; Inani, Sarveshwar
Abstract: The study investigates price discovery in the Indian stock market and finds that spot market plays a dominating role in price discovery when it is estimated for the entire period as a whole. However, periodic measures of price discovery suggest that it does not remain the same throughout the period, but varies with time. Panel data analysis also indicates that spot market is more efficient in price discovery for majority of size and sector panels. Finally, while market state‐related variables are found to impact information shares in a majority of the cases, macroeconomic announcements rarely predict the price discovery.